Karakterisasi dan Uji Aktivitas Antimikroba Bakteri Kandidat Probiotik dari Terasi Udang Rebon - Herlinda Mawardika; Krisna Kharisma Pertiwi; Dwi Wahyuni; Qosania Wilda Aulia (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Probiotics are live microorganisms that are widely used to help maintain a healthy digestive system. Some compounds secreted by these bacteria have a bactericidal effect on pathogenic and putrefactive bacteria. Various types of probiotic bacteria can be obtained from fermented foods and drinks. This research aims to characterize bacteria from rebon shrimp paste in Macajah Village, Tanjung Bumi District, Bangkalan Regency, East Java Province which have potential as probiotics and test their antimicrobial activity against pathogenic bacteria. Bacteria were isolated using the Pour Plate technique using de Man Rogosa Sharpe Agar media. The bacterial isolates were then characterized by observing colony morphology, cells and biochemical properties. Next, antibacterial activity was tested using the well diffusion method. The results showed that the four bacteria obtained from the samples were gram positive, round and rod shaped, catalase negative, homofermentative, grew at a temperature of 37-45°C, survived at NaCl concentrations of 4 and 6.5%, low pH, and bile salts. According to the characterization results, three bacterial isolates belonged to the genus Enterococcus and one other isolate belonged to the genus Bacillus. Bacillus isolate is a potential probiotic candidate, because it has inhibitory activity against Escherichia coli and Staphylococcus aureus.